The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s0102-05362002000100007
|View full text |Cite
|
Sign up to set email alerts
|

Calidad postcosecha de tomates almacenados en atmósferas controladas

Abstract: Las atmósferas controladas alargan la vida en estante del tomate, permitiendo su cosecha en estados de madurez más avanzados y a su vez afectando su calidad. El objetivo de este experimento fue estudiar los efectos que atmósferas controladas con bajas concentraciones de oxígeno y libres de dióxido de carbono y etileno, producen sobre el color, la firmeza y los principales componentes del sabor de frutos de tomate cultivar Diva. Durante abril de 1998, frutos cosechados con grado de color 3 (USDA) en INTA Balcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 15 publications
1
10
0
9
Order By: Relevance
“…The pH of tomatoes stored at 7 and 22 °C did not significantly changed (p > 0.05); while at 37 °C, the pH was increased (p < 0.05). Gómez and Camelo (2002) reported that during the storage of tomatoes in controlled atmosphere (12 °C), the pH slightly increased. In general, the titratable acidity was 0.3 ± 0.0% (citric acid), and was under the reported by other researchers, like Wold et al (2004); they informed a titratable acidity of 0.44-0.77%.…”
Section: Discussionmentioning
confidence: 99%
“…The pH of tomatoes stored at 7 and 22 °C did not significantly changed (p > 0.05); while at 37 °C, the pH was increased (p < 0.05). Gómez and Camelo (2002) reported that during the storage of tomatoes in controlled atmosphere (12 °C), the pH slightly increased. In general, the titratable acidity was 0.3 ± 0.0% (citric acid), and was under the reported by other researchers, like Wold et al (2004); they informed a titratable acidity of 0.44-0.77%.…”
Section: Discussionmentioning
confidence: 99%
“…The titratable acidity was determined using the methodology of Gómez and Camelo (2002) using the following formula.…”
Section: Resultados Y Discusiónmentioning
confidence: 99%
“…Of the soluble solids, approximately 60% are sugars, mainly glucose and fructose (Gómez and Camelo, 2002), since the plant is highly necessary an adequate supply of these, nutrition and management are very important to achieve this goal (Reuscher et al, 2014). Among other important factors, nutrition is essential for an adequate concentration of °Brix in marketable fruits.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations